Detailed Functional and Proteomic Characterization of Fludarabine Resistance in Mantle Cell Lymphoma Cells - Lorkova, Lucie; Scigelova, Michaela; Arrey, Tabiwang Ndipanquang; Vit, Ondrej; Pospisilova, Jana; Doktorova, Eliska; Klanova, Magdalena; Alam, Mahmudul; Vockova, Petra; Maswabi, Bokang; Klener, Pavel; Petrak, Jiri (PloS one, 2015)
Mantle cell lymphoma (MCL) is a chronically relapsing aggressive type of B-cell non-Hodgkin lymphoma considered incurable by currently used treatment approaches. Fludarabine is a purine analog clinically still widely used in the therapy of relapsed MCL. Molecular mechanisms of fludarabine resistance have not, however, been studied in the setting of MCL so far. We therefore derived fludarabine-resistant MCL cells (Mino/FR) and performed their detailed functional and proteomic characterization compared to the original fludarabine sensitive cells (Mino). We demonstrated that Mino/FR were highly cross-resistant to other antinucleosides (cytarabine, cladribine, gemcitabine) and to an inhibitor of Bruton tyrosine kinase (BTK) ibrutinib. Sensitivity to other types of anti-lymphoma agents was altered only mildly (methotrexate, doxorubicin, bortezomib) or remained unaffacted (cisplatin, bendamustine). The detailed proteomic analysis of Mino/FR compared to Mino cells unveiled over 300 differentially expressed proteins. Mino/FR were characterized by the marked downregulation of deoxycytidine kinase (dCK) and BTK (thus explaining the observed crossresistance to antinucleosides and ibrutinib), but also by the upregulation of several enzymes of de novo nucleotide synthesis, as well as the up-regulation of the numerous proteins of DNA repair and replication. The significant upregulation of the key antiapoptotic protein Bcl-2 in Mino/FR cells was associated with the markedly increased sensitivity of the fludarabine-resistant MCL cells to Bcl-2-specific inhibitor ABT199 compared to fludarabine-sensitive cells. Our data thus demonstrate that a detailed molecular analysis of drug-resistant tumor cells can indeed open a way to personalized therapy of resistant malignancies.
Keywords: Isotope Labeling; Chromatography, Liquid; Lymphoma, Mantle-Cell; Male; vidarabin; protinádorové látky; lymfom z plášťových buněk; Vidarabine; tandemová hmotnostní spektrometrie; chemorezistence; mužské pohlaví; chromatografie kapalinová; proteomika; lidé; izotopové značení; Humans; nádorové buňky kultivované; Tumor Cells, Cultured; Drug Resistance, Neoplasm; Proteomics; Tandem Mass Spectrometry; Biomarkers, Tumor; nádorové biomarkery; Antineoplastic Agents